Motivasi dan Kinerja: Pemoderasian Kepribadian Conscientiousness dan Openness - Dyah Handayani Dewi (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
Purpose The purpose of this study is to examine the role of personality as part of the individual characteristics that moderate the relationship between motivation and performance. Methodology Sample size with 115 respondents from two advertising companies. SPSS 26 with Macro Process model no 2 is running. Findings The test results reveal that increasing external motivation will improve performance. The effect of motivation on performance is moderated by conscientiousness and openness personality. Suggestion This research provides benefits in the application of recruitment and selection for advertising companies to recruit someone with an openness personality.